Winter garden [compact disc, unabridged] - Hannah, Kristin (Brilliance Audio, 2010)
Meredith and Nina Whitson are as different as sisters can be. One stayed at home to raise her children and manage the family apple orchard; the other followed a dream and traveled the world to become a famous photojournalist. But when their beloved father fails ill, Meredith and Nina find themselves together again, standing alongside their cold, disapproving mother, Anya, who even now offers no comfort to her daughters.